Chrześcijański demokrata wobec kryzysu demokracji w Europie lat trzydziestych: przypadek Alcide De Gasperiego - Pazik, Przemysław (Dzieje Najnowsze, 2016)
The text embarks upon the motif of the evolution of the political reflections of Alcide De Gasperi, one of the key Italian politicians of the interwar period and the Prime Minister of Italy after 1945, in the face of a crisis of the democracy during the 1930s. The basic source for a reconstruction of De Gasperi’s views are the commentaries about international politics written by this Italian Christian Democrat for the bi-weekly ”l’Illustrazione Vaticana” in 1933–1938. By following the way in which he described political dynamics in Germany, France, and Spain it is possible to perceive the key topics of De Gasperi’s deliberations about politics in general: a defence of parliamentarianism, a critique of the pre-1929 free-market economy, and the need for a new social order, which the Italian politician discovered in personalism. Those three motifs merge in descriptions and assessments of events transpiring in the above–mentioned countries; moreover, they compromise the prime axes of the transformation of the Italian Christian-democratic doctrine into a mature ideology of a ruling party, which the Christian Democracy became after 1945.